Cellular uptake of multilayered capsules produced with natural and genetically engineered biomimetic macromolecules - Costa, Rui R. (2014)
Multilayered microcapsules of chitosan and biomimetic elastin-like recombinamers (ELRs) were prepared envisaging the intracellular delivery of active agents. Two ELRs containing either a bioactive RGD sequence or a scrambled non-functional RDG were used to construct two types of functionalized polymeric microcapsules, both of spherical shape ∼4μm in diameter. Cell viability studies with human mesenchymal stem cells (hMSCs) were performed using microcapsule/cell ratios between 5:1 and 100:1. After 3 and 72h of co-incubation, no signs of cytotoxicity were found, but cells incubated with RGD-functionalized microcapsules exhibited higher viability values than RDG cells. The internalization efficacy and bioavailability of encapsulated DQ-ovalbumin were assessed by monitoring the fluorescence changes in the cargo. The data show that surface functionalization did not significantly influence internalization by hMSCs, but the bioavailability of DQ-ovalbumin degraded faster when encapsulated within RGD-functionalized microcapsules. The microcapsules developed show promise for intracellular drug delivery with increased drug efficacy.